Study on expression of cytokine genes in peripheral blood mononuclear cells (PBMCs) following Hepatitis B vaccination (Bangladesh Journal of Physiology and Pharmacology, 2014)
Vaccination with surface protein of Hepatitis B Virus (HBsAg) is considered the main strategy for effective control of the infection and viral transmission. The present study was designed to determine the expression of Interferon (INF-?) in peripheral blood mononuclear cells (PBMCs) by RT-PCR method. In the present study, PBMCs from responders expressed INF-? gene in response to HBsAg, while nonresponders expressed low levels of this cytokines. Most humoral non responders to HBV thus develop specific cellular immune responses, eventually liable to protect them against viral infection. http://dx.doi.org/10.3329/bjpp.v29i1-2.20064 Bangladesh J Physiol Pharmacol 2013; 29(1&2) : 25-28